Livelihood implications of in situ conservation strategies of wild fruit tree species in Uzbekistan - Gotor, Elisabetta; Caracciolo, Francesco; Elias, Marlène; Trincia, C. (Bioversity International, 2015)
Throughout 2006 and 2011, Bioversity International has been promoting the conservation and use of plant genetic diversity in Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan and Uzbekistan under the auspices of the United Nations Environment Programme (UNEP) and Global Environment Facility (GEF).After 2013, an impact assessment study was carried out to examine whether the tangible benefits of the Bioversity International project were transferred at the household level, with specific emphasis on Uzbekistan, selected for the country relevance in terms of household characteristics and area covered by the project.In particular, the assessment focused on the effects of the interventions in the activity areas involving the enhancement of use and consumption of target fruits, as well as of their marketing value, to improve household food security and wellbeing.